A systematic review of the sensitivity and specificity of the toe–brachial index for detecting peripheral artery disease. (August 2016) - Tehan, Peta Ellen; Santos, Derek; Chuter, Vivienne Helaine
The toe–brachial index (TBI) is used as an adjunct to the ankle–brachial index (ABI) for non-invasive lower limb vascular screening. With increasing evidence suggesting limitations of the ABI for diagnosis of vascular complications, particularly in specific populations including diabetes cohorts, the TBI is being used more widely. The aim of this review was to determine the sensitivity and specificity of the TBI for detecting peripheral artery disease (PAD) in populations at risk of this disease. A database search was conducted to identify current work relating to the sensitivity and specificity of toe–brachial indices up to July 2015. Only studies using valid diagnostic imaging as a reference standard were included. The QUADAS-2 tool was used to critically appraise included articles. Seven studies met the inclusion criteria. Sensitivity of the TBI for PAD was reported in all seven studies and ranged from 45% to 100%; specificity was reported by five studies only and ranged from 16% to 100%. In conclusion, this review suggests that the TBI has variable diagnostic accuracy for the presence of PAD in specific populations at risk of developing the disease. There was a notable lack of large-scale diagnostic accuracy studies determining the diagnostic accuracy of the TBI in detecting PAD in different at-risk cohorts. However, standardised normal values need to be established for the TBI to conclusively determine the diagnostic accuracy of this test.